FATHER’S ROLES IN JESSI NELSON’S '' I AM SAM '' - Ade Sulfaida Suaib Ladia; Olga Rorintulus; Sarah Kamagi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
This study is carried to describe the father’s roles depicted by the main character in the movie "I AM SAM" by Jessi Nelson.  The study is focused on the father’s role depicted by Sam as Lucy’s father who is psychologically retarded. This research applies qualitative research design.  In carrying out this research, the data are obtained from the movie by Jessi Nelson entitled I am Sam as primary source and also supported by other relevant references such as books, documents and web sources as secondary sources. In doing the data analysis, the researcher uses objective approach. The result shows that Sam is a good father figure for Lucy whose roles are influential although in his disability namely assisting and giving affection, fighting for custody, seeking lawyer in court and motivating to socialize. He also doesn't want to force perfection since he is retarded but does not lower his spirit to rasie Lucy the daughter. Sam puts forward about how parents treat their children. Here it can be seen how a person's intellectual capacity or IQ does not hinder the affection that parents give to their children, as well as affection for other people. The main thing every child raised by his parents is in need of love and a mentally retarded person is not deterred from giving that.